2006
DOI: 10.1007/s00227-005-0231-y
|View full text |Cite
|
Sign up to set email alerts
|

Population biology and life strategies of Chlorophthalmus agassizii Bonaparte, 1840 (Pisces: Osteichthyes) in the Mediterranean Sea

Abstract: The population biology and life strategies of Chlorophthalmus agassizii were studied in the Ionian Sea (eastern–central Mediterranean) using the data collected during the experimental trawl surveys carried out from 1995 to 2000. Depth-related trends of both density and size were found. With depth the former decreased while the latter increased. A typical bigger–deeper phenomenon was detected: young-of-the-year individuals occur on the shelf during autumn–winter months and move towards bathyal bottoms as they g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In general, size‐related diet composition is governed mainly by the change of habitat between the smaller and larger individuals (Macpherson and Duarte, 1991). Considerating that the distribution of C. agassizi in the above area showed a clear size‐related depth distribution pattern (‘bigger–deeper’ phenomenon, Anastasopoulou et al., 2006; D’Onghia et al., 2006), suggests that the different preferences observed between small : large individuals reflect the depth changes in the food supply. Thus, the food items of medium and larger individuals were more associated with the sea bottom (epibenthic food types found in their stomach samples, such as polychaetes, hydrozoa, mud), which were not found in the stomach contents of the smaller group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In general, size‐related diet composition is governed mainly by the change of habitat between the smaller and larger individuals (Macpherson and Duarte, 1991). Considerating that the distribution of C. agassizi in the above area showed a clear size‐related depth distribution pattern (‘bigger–deeper’ phenomenon, Anastasopoulou et al., 2006; D’Onghia et al., 2006), suggests that the different preferences observed between small : large individuals reflect the depth changes in the food supply. Thus, the food items of medium and larger individuals were more associated with the sea bottom (epibenthic food types found in their stomach samples, such as polychaetes, hydrozoa, mud), which were not found in the stomach contents of the smaller group.…”
Section: Discussionmentioning
confidence: 96%
“…Despite its abundance, highly important ecological information such as growth, biology and the distribution of the species in the Greek Ionian Sea is scarce. Only two studies have been carried out in the Greek Ionian Sea concerning the distribution and some aspects of the biology of this species (Anastasopoulou et al., 2006; D’Onghia et al., 2006). Very few data concerning the feeding habits of C. agassizi in the Mediterranean basin exist in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, deep sea fishes have been viewed as continuously reproductive given the stability of their environment. More recently, distinct seasonal reproductive cycles have emerged (D'Onghia et al, ). Deep sea fishes may also sync reproductive cycles via vertical migrations of mesopelagic fauna (Merrett, ; Gage and Tyler, ).…”
Section: Discussionmentioning
confidence: 99%
“…Deep sea fishes may also sync reproductive cycles via vertical migrations of mesopelagic fauna (Merrett, ; Gage and Tyler, ). Typically, adult fishes spawn with buoyant eggs rising upwards to shallower water where fertilized ova develop and larva then undergo ontogenic migrations to deeper water (Fernandez‐Arcaya et al, ; D'Onghia et al, ; Lin et al, ). However, we observed that mature ovarian follicles did not contain oil globules, similar to other accounts of oarfish (Honma et al, ) and the related opah ( Lampris guttatus ; Lampridiformes; Olney, ), which complicates the complete understanding of oarfish reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…A longer spawning period also indicates that favourable environmental conditions for hatching and larval development are available for a longer period (Gonçalves andErzini 2000, Pajuelo et al 2006). However this species, shows a longevity of more than 10 years (D'Onghia et al 2006) and a relatively late maturation, which are considered important with respect to management (Booth and Buxton 1997). These characteristics make the species more vulnerable to fishing exploitation and can result in possible overfishing.…”
Section: Discussionmentioning
confidence: 99%